A Phenomenographic Study of Adolescents’ Conceptions of Health Information Appraisal as a Critical Component of Adolescent Health Literacy - Stars, Inese; Rubene, Zanda (Acta Paedagogica Vilnensia, 2020)
This paper reports on a health literacy study that explored adolescents’ conceptualizations of health information appraisal as a social practice in Latvia. The study was guided by phenomenography, a qualitative research approach used to describe people’s conceptions of a particular phenomenon. A purposive, maximum variation sampling was used, and 24 adolescents were recruited to take part in the study, ranging from 13 to 16 year-olds. Semi-structured interviews were undertaken for data collection. A phenomenographic method for data analysis was performed using the guidelines proved by Sandberg. The data analysis presented seven categories of description and an outcome space representing the adolescents’ qualitatively different conceptions of health information appraisal. The implications for health education in school are discussed.
Keywords: adolescents; health literacy; information appraisal; health education; phenomenography